Family History and Prior Allergies of Cancers and the Risk of Adult Leukemia in Shandong Province, China - HC Wang; HL Lin; N Shao; JR Zhang; J Zou; CY Ji (Tehran University of Medical Sciences, 2012)
Background: A case-control study was carried out to investigate the roles of prior allergies and family history of cancers and their interaction in the etiology of adult leukemia. Methods: Prior allergies status and family history of cancers in first-degree relatives were compared between 131 incident leukemia cases and 206 hospital-based controls. Odds ratios (OR) were estimated using an unconditional regression model taking into account potential confounding factors. Results: Significant association between adult leukemia and prior allergies and family history of cancer (OR=2.09, 95% CI: 1.22-3.58 for prior allergies; and OR=2.35, 95% CI: 1.09-5.03 for family history of cancer, OR=15.88, 95% CI: 1.77-142.55 for both the two factors (+), respectively) was found after adjusting for potential confounding factors. Conclusion: Prior allergies and family history of cancers may be risk factors for adult leukemia; their interaction was likely to be synergistic rather than additive for the risk of leukemia.